2019
DOI: 10.1029/2018ms001595
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Modeling Irrigation From Field to Regional Scales

Abstract: Correctly calculating the timing and amount of crop irrigation is crucial for capturing irrigation effects on surface water and energy budgets and land‐atmosphere interactions. This study incorporated a dynamic irrigation scheme into the Noah with multiparameterization land surface model and investigated three methods of determining crop growing season length by agriculture management data. The irrigation scheme was assessed at field scales using observations from two contrasting (irrigated and rainfed) AmeriF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 61 publications
(155 reference statements)
0
57
0
Order By: Relevance
“…The Noah‐MP‐Crop model was implemented in the High‐Resolution Land Data Assimilation System (F. Chen et al., 2007) and Weather Research and Forecasting model (Skamarock et al., 2007). It improves the simulations of vegetation dynamics and surface heat fluxes for corn and soybean at both field and regional scales by using a number of agricultural management data, such as growing degree days (GDDs) and planting/harvesting dates (X. Liu et al., 2016, 2020; Xu, Chen, et al., 2019; Z. Zhang et al., 2020). However, uncertainties in input data, model structures, and model parameters inevitably induce uncertainties in the variables simulated by those process‐based models (X. Li et al., 2007; T. Xu et al., 2011; Zhang, Chen, & Gan, 2016; Zhang, Guanter, et al., 2016; Zhang, Xiao, et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Noah‐MP‐Crop model was implemented in the High‐Resolution Land Data Assimilation System (F. Chen et al., 2007) and Weather Research and Forecasting model (Skamarock et al., 2007). It improves the simulations of vegetation dynamics and surface heat fluxes for corn and soybean at both field and regional scales by using a number of agricultural management data, such as growing degree days (GDDs) and planting/harvesting dates (X. Liu et al., 2016, 2020; Xu, Chen, et al., 2019; Z. Zhang et al., 2020). However, uncertainties in input data, model structures, and model parameters inevitably induce uncertainties in the variables simulated by those process‐based models (X. Li et al., 2007; T. Xu et al., 2011; Zhang, Chen, & Gan, 2016; Zhang, Guanter, et al., 2016; Zhang, Xiao, et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation (DA) methods originated from estimation theory and cybernetics to merge observational information into process‐based models to mitigate uncertainties in model variables and optimize model parameters (X. Li et al., 2020; Liang & Qin, 2008; Xia et al., 2019). This is done within variational‐based or ensemble‐based DA schemes to improve the model performances (He, Xu, et al., 2019; He, Xu, Bateni, et al., 2020; He et al., 2018; Lu et al., 2016, 2017, 2020; Margulis et al., 2002; Xu, Bateni, et al., 2018; Xu, Chen, et al., 2019; Xu, He, et al., 2019; T. Xu et al., 2011, 2015). Studies have assimilated various observational variables such as land surface temperature (LST), leaf area index (LAI), soil moisture (SM), and solar‐induced chlorophyll fluorescence (SIF) into crop models and/or LSMs, which has improved the estimated crop yields (Ines et al., 2013; X. Li et al., 2018; Wang et al., 2014; Xie et al., 2017), vegetation biomass, evapotranspiration (ET), and gross primary production (GPP) within LSMs (Huang et al., 2008; Kumar et al., 2019; Xu, He, et al., 2019; T. Xu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such perturbations in surface energy and water fluxes not only lead to surface cooling and decreases in Bowen ratios that modulate boundary layer evolution and convective processes in the atmosphere (DeAngelis et al, 2010; Harding & Snyder, 2012; Pei et al, 2016) but also influence the hydrologic budget. For example, previous studies (Leng et al, 2015; Qiu et al, 2019; Xu et al, 2019) have demonstrated that the hydrologic budget terms such as infiltration, percolation to deep soil layers, recharge to aquifers, and in turn baseflow at field, watershed, and large basin scales can be altered by irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed research needs to be performed by combining observational data and modeling because the conclusions may vary depending on the scale (Xu et al, 2019). Other il-luminating work with regional models showed that the combined effect of UHIs and aerosols on precipitation depends on synoptic conditions (Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%